Islam and university education in contemporary Nigeria (2008)
This paper examines the contemporary problems confronting education in the Islamic world and critiques effort already put in place to solve them. It begins with an excursus into classical history of Islamic education and proceeds from there to discuss the politics and inherent challenges facing tertiary education particularly in Nigeria. It concludes that a pragmatic approach to solving the identified problems would be the adoption of Islamic philosophy which emphasizes a non-utilitarian approach to education as a whole.